2010
DOI: 10.1212/wnl.0b013e3181ccc6ef
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin for painful HIV neuropathy

Abstract: Objective: Pregabalin is effective in several neuropathic pain syndromes. This trial evaluated its efficacy, safety, and tolerability for treatment of painful HIV-associated neuropathy.Methods: This randomized, double-blind, placebo-controlled, parallel-group trial included a 2-week double-blind dose-adjustment (150 -600 mg/day BID) phase, a 12-week double-blind maintenance phase, and an optional 3-month open label extension phase. The primary efficacy measure was the mean Numeric Pain Rating Scale (NPRS) scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 32 publications
(50 reference statements)
3
122
0
7
Order By: Relevance
“…[71][72][73][74][75][76][77] It is unclear whether these results reflect a true lack of efficacy in the specific conditions studied or whether other factors have accounted for the lack of success in demonstrating efficacy (eg, inadequate power to detect modest treatment benefits, excessive response rates in placebo groups, other methodological features of the trials).…”
Section: Negative Trials Of Pharmacological Treatments For Np and Thementioning
confidence: 99%
See 1 more Smart Citation
“…[71][72][73][74][75][76][77] It is unclear whether these results reflect a true lack of efficacy in the specific conditions studied or whether other factors have accounted for the lack of success in demonstrating efficacy (eg, inadequate power to detect modest treatment benefits, excessive response rates in placebo groups, other methodological features of the trials).…”
Section: Negative Trials Of Pharmacological Treatments For Np and Thementioning
confidence: 99%
“…The first indication of this was the publication in 1998 of 2 placebo-controlled RCTs in which amitriptyline failed to relieve pain in patients with painful HIV neuropathy, 80,81 which has been followed by negative trials of topical lidocaine 82 and pregabalin 76 in HIV neuropathy. The results of a recent negative trial of memantine in HIV neuropathy 83 are more difficult to interpret because memantine is considered a third-line NP treatment on the basis of inconsistent evidence of efficacy.…”
Section: 79mentioning
confidence: 99%
“…Subgroup analysis of a randomized controlled trial of pregabalin in HIV-SN has reported a small group of patients with signs of mechanical sensory gain [44]. Furthermore, by using the Neuropathic Pain Symptom Inventory it has been revealed that 42% of participants experiencing painful HIV-SN report symptoms of moderate and severe cold evoked pain, although this is not detected with sensory profiling [40].…”
Section: Systemic Indinavir Induces a Minimal Spinal Microglial Respomentioning
confidence: 99%
“…A recently published review and meta-analysis describes randomized controlled trials (RCT`s) evidence of analgesic efficacy superior to placebo in the context of HIV-SN pain only for smoked cannabis, recombinant nerve growth factor (rhNGF) and high dose (8%) topical capsaicin [48]. Several other agents have been examined in RCTs and found to be not effective such as acetyl-L carnitine (1g/day), amitriptyline (100mg/day), topical capsaicin 0.075%, gabapentin (2.4g/day), mexilitine (600mg/day), peptide -T (6mg/day), pregabalin (600mg/day), lamotrigine (600mg/day) and prosaptide (16mg/day) [48, (Simpson, Schifitto et al 2010)]. Prospective RCT´s show however an effectiveness for gabapentin (up to 3.6g/d) [49] in HIV-DSP as well as lamotrigene in ATN [50].…”
Section: Wwwintechopencommentioning
confidence: 99%